Intravitreal clindamycin in the treatment of ocular toxoplasmosis: a report of two cases - Rogaczewska, Małgorzata; Stopa, Marcin (Klinika Oczna / Acta Ophthalmologica Polonica, 2021)
We present a report of two patients with active ocular toxoplasmosis treated with intravitreal clindamycin. The location of the retinochoroiditis close to the optic disc validated the injection of 1 mg clindamycin, even though the visual acuity was not diminished. After 7 days, inflammatory lesions and vitritis regressed significantly. Moreover, no side effects occurred.